STRENGTHENING EARLY CHILHOOD EDUCATION QUALITY THROUGH PRINCIPAL ACADEMIC SUPERVISION WITH ISLAM VALUE - Nofi Wulandari; Nurkolis Nurkolis; Muhammad Prayito (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
Academic supervision plays a strategic role in ensuring sustainable learning quality in early childhood education. This study examines how academic supervision supports the improvement of learning quality at TK Nasima Semarang while situating the findings within the broader context of instructional leadership and child-centered pedagogy. The study is grounded in the need to ensure that supervision functions not merely as an administrative evaluative process, but evolves into reflective, collaborative, and value-oriented professional development. Using a descriptive qualitative approach, data were collected through semi-structured interviews, classroom observations, and document analysis. The findings show that academic supervision is implemented as a continuous cycle involving systematic planning, direct and digital observation, reflective dialogue, and sustained professional development support. Teachers reported improvements in teaching readiness, pedagogical reflection, and their capacity to respond to children’s diverse developmental needs. Parents also observed increased enthusiasm and engagement among children during learning activities. The study further reveals that the supervision process not only enhances pedagogical competence but also strengthens value-based teaching practices, including modeling, empathy, and the cultivation of Islamic character traits relevant to early childhood moral development. The study concludes that academic supervision conducted in a structured, reflective, and collaborative manner significantly contributes to the improvement of learning quality, the strengthening of teacher professionalism, and the character development of young learners. These findings underscore the importance of technology integration, teacher collaboration, and adaptive supervision approaches within value-based early childhood education settings. Moreover, the study opens avenues for further exploration of digital supervision and long-term professional development oriented toward high-quality, character-based learning.